Sustainable AgriVentures for Empowered Women and Youth (SAVE-WY) Intervention Program in Zimbabwe - Rukasha, T.; Musemwa, L.; Mokhema, Seipati (International Water Management Institute (IWMI). CGIAR Initiative on Diversification in East and Southern Africa, 2024)
The Sustainable AgriVentures for Empowered Women and Youth (SAVE-WY) project is implemented by Marondera University of Agricultural Science and Technology in partnership with Bindura University of Science Education. This project is supported financially by the International Water Management Institute in South Africa and is an Ukama Ustawi Work Package 5 Project activity. Funded by CGIAR with a budget of USD 45,000, the SAVE-WY project targeted 150 households in Mashonaland Central and Masvingo provinces of Zimbabwe.